2019
DOI: 10.1016/j.arthro.2019.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Anterior Cruciate Ligament Reconstruction Using Biologic Augmentation in Patients 21 Years of Age and Younger

Abstract: Purpose: To report on the outcomes of a subset of patients 21 years of age after anterior cruciate ligament (ACL) reconstruction coupled with biologic augmentation using platelet-rich plasma (PRP) and a porous collagen carrier. Methods: A cohort of patients was retrospectively reviewed after ACL reconstruction with hamstring autograft tendon. All reconstructive surgeries combined biologic augmentation in which the ACL graft was coupled with PRP contained within porous collagen membrane. Patients were included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 28 publications
0
21
0
1
Order By: Relevance
“…Several articles have discussed the risk of ACLR failure associated with allograft tissue [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. A significant increase in ACLR failure has been shown in young patients who received allograft tissue in their reconstruction procedures [10][11][12][13]19]. Kaeding et al, in a review of the data from the Multicenter Orthopaedic Outcomes Network (MOON) trials, found a four times higher ACLR graft failure rate when using allograft versus autograft in the population of 10-19 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several articles have discussed the risk of ACLR failure associated with allograft tissue [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. A significant increase in ACLR failure has been shown in young patients who received allograft tissue in their reconstruction procedures [10][11][12][13]19]. Kaeding et al, in a review of the data from the Multicenter Orthopaedic Outcomes Network (MOON) trials, found a four times higher ACLR graft failure rate when using allograft versus autograft in the population of 10-19 years.…”
Section: Discussionmentioning
confidence: 99%
“…Delay in biologic graft incorporation has been of primary concern when considering allograft failures [19][20][21]. Rappé et al found a 33% failure rate when using irradiated Achilles tendon allografts to a 2.4% failure rate when using nonirradiated Achilles tendon allografts [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…I n the Level IV study, "Outcomes of Anterior Cruciate Ligament Reconstruction Using Biologic Augmentation in Patients 21 Years of Age and Younger," 1 Berdis, Veale, and Fleissner report on 143 patients who underwent a primary hamstring anterior cruciate ligament (ACL) reconstruction coupled with a platelet-rich plasma (PRP)/collagen membrane augmentation. At an average duration of follow-up of 52 months, their KT-1000 sideto-side difference averaged 1.2 mm.…”
Section: See Related Article On Page 3107mentioning
confidence: 99%